Microorganism population in two-phase anaerobic fermentation of separated liquid of dairy manure - Li, Qiang; Guan, Zhengjun; Zheng, Guoxiang (International Journal of Agricultural and Biological Engineering, 2018)
In order to reduce incomplete fermentation caused by high substrate viscosity and low mass transfer efficiency during fermentation process, batch and two-phase anaerobic fermentation experiments were conducted in this study. Dairy manure was separated by using solid-liquid separator firstly. Separated liquid (SL) and diluted dairy manure (DDM) as raw materials were evaluated in terms of gas production performance for both batch and two-phase anaerobic fermentation. The microorganism population was characterized by scanning electron microscope (SEM) and Denaturing Gradient Gel Electrophoresis (DGGE). The results showed that Volatile Solid (VS) methane yield of SL was 124.51 L/kg VS, which was 2.09 times higher than that of DDM (59.50 L/kg VS) in batch anaerobic fermentation. The Bacteroides and Veillonella with higher activity were the majority microorganism population in acidogenic phase, whereas the Firmicutes and Corynebacterium with methanogenic properties became the predominant microorganism population in methanogenic phase. This study achieved the phase separation and improved the gas production performance.Keywords: separated liquid, diluted dairy manure, two-phase anaerobic fermentation, microorganism, scanning electron microscope (SEM), Denaturing Gradient Gel Electrophoresis (DGGE)DOI: 10.25165/j.ijabe.20181101.3206Citation: Li Q, Guan Z J, Zheng G X. Microorganism population in two-phase anaerobic fermentation of separated liquid of dairy manure. Int J Agric & Biol Eng, 2018; 11(1): 206–211.